Curriculum Design for Digital Financial Innovation in Higher Education Institutions in Indonesia - Simatupang, Batara Maju (Jurnal Manajemen Teknologi, 2022)
Abstract. Due to rapid technological advancement, the financial industry is now transitioning from traditional to digitally based financial services. In Indonesia in particular, this transformation is being carried out in accordance with the idea of digital finance innovation. However, within the Indonesian financial industry, there is a competency gap that hinders the rate of progress of this transformation. Accordingly, this study aims to create a curriculum designed explicitly for digital finance innovation for Indonesian higher education institutions in order to address the existing competency gap. Through the application of multivariate regression analysis, eight required competencies and their respective subjects were identified in this study. The identified competencies can provide insights for higher education institutions in creating a curriculum to ensure that their future graduates can fill the competency gap within the Indonesian financial industry. The results of the study state that: (i) an effective and appropriate relationship between DA, RM, BM, and SM competencies and can improve the ability of financial institutions to identify and manage risks in their environment; (ii) the relationship between FIK knowledge and PRO and BM competencies can help financial institutions ensure that their DFI products, such as applications, meet the standards set by regulators and improve management practices; (iii) the relationship between FL and PRO competencies can improve the organization's ability to reduce the possibility of miscommunication and misperceptions surrounding DFI ideas. Hence, these findings have implications for the university curriculum that implements them, bolstering the output of graduates who can help accelerate the actualization of the digital financial innovation agendas of the Indonesian financial industry.Keywords: digital finance innovation; financial technology; higher education institutions Abstrak. Dengan pesatnya kemajuan teknologi yang terjadi, industri keuangan kini berada pada fase transisi dari layanan keuangan tradisional ke layanan keuangan berbasis digital. Khusus di Indonesia, transformasi dilakukan dengan mengikuti ide inovasi keuangan digital. Namun, dalam industri keuangan Indonesia, terdapat gap kompetensi yang menghambat laju kemajuan transformasi. Oleh karena itu, penelitian ini bertujuan untuk membuat kurikulum yang dirancang secara eksplisit di bawah inovasi keuangan digital untuk institusi pendidikan tinggi di Indonesia dalam rangka mengatasi kesenjangan kompetensi yang ada. Melalui penerapan analisis regresi multivariat delapan kompetensi yang dibutuhkan dan subjek masing-masing diidentifikasi. Kompetensi yang teridentifikasi dapat memberikan wawasan bagi institusi pendidikan tinggi dalam membuat kurikulum untuk memastikan lulusan masa depan mereka dapat mengisi gap kompetensi di industri keuangan Indonesia. Hasil penelitian menyatakan bahwa (i) Hubungan yang efektif dan tepat antara kompetensi DA, RM, BM, dan SM dapat meningkatkan kemampuan lembaga keuangan dalam mengidentifikasi dan mengelola risiko berada di dalam lingkungannya, (ii) Hubungan antar pengetahuan FIK dengan kompetensi PRO dan BM dapat membantu lembaga keuangan memastikan produk IKD mereka seperti aplikasi dalam memenuhi standar yang ditentukan oleh regulator seiring dengan peningkatan praktik manajemen dan (iii) Hubungan antara kompetensi FL dan PRO dapat meningkatkan kemampuan organisasi untuk mengurangi kemungkinan miskomunikasi dan persepsi yang salah tentang ide IKD. Oleh karena itu, hasil temuan ini berimplikasi bagi Kurrikulum PT yang menerapkannya, memungkinkan output lulusannya dapat membantu industri keuangan Indonesia mempercepat aktualisasi agenda inovasi keuangan digitalKatakunci: inovasi keuangan digital, teknologi keuangan, institusi pendidikan tinggi.